A Analisis Faktor Yang Mempengaruhi Ketergantungan Penggunaan Chatgpt Pada Pengerjaan Tugas Mahasiswa Universitas Mataram - Arbyati, Asri Mustika; Apriliana, Baiq Nurul; Putri, Devi Karina; Aisya, Hakiki Latifa; Putri, Dina Eka; Baskara, Zulhan Widya; Zulhan Widya Baskara (Program Studi Matematika, 2025)
The use of artificial intelligence technology, such as ChatGPT, is increasing among students to support their academic assignments. However, dependence on this technology needs to be analyzed to understand the factors that influence it. This study aims to analyze the factors that influence the dependence on the use of ChatGPT in completing assignments of Mataram University students. Sampling was carried out using the quota sampling method, involving 98 respondents who were Mataram University students and ChatGPT users. The method used was multiple linear regression to evaluate the effect of independent variables on dependence, and factor analysis to identify the structure of these variables. Based on the results of the analysis, one main factor was found which was formed from four variables, namely ChatGPT Ease of Use, ChatGPT Reliability, User Satisfaction, and Perceived Benefits. This main factor was able to explain 71.73% of the total data variation, which showed a significant contribution to students' dependence on using ChatGPT. Thus, this study shows that these variables are interrelated and influence the level of students' dependence on ChatGPT in completing academic assignments.